The young eyewitness : how well do children and adolescents describe and identify perpetrators? - Pozzulo, Joanna (American Psychological Association, 2017)
"Every year, numerous crimes occur involving child eyewitnesses. In some cases, children are the only eyewitnesses, which makes them especially critical for solving the cases. But how reliable is child eyewitness evidence? This book summarizes the research on how well children can describe an event and perpetrator (which is a recall task) and how well they can identify the perpetrator in person or in photographs (which is a recognition task). It shows that although children may be less advanced in these skills than adults, they nonetheless can provide invaluable evidence. Pozzulo interprets the research in light of developmental theories, and notes practical implications for forensic investigations. In particular, the chapters highlight interviewing techniques to facilitate accurate recall and lineup techniques to facilitate accurate recognition. This book is an essential resource for all forensic investigators"--Publicity materials. (PsycINFO Database Record (c) 2016 APA, all rights reserved).